Judicial Inconsistency in Theft Sentencing: A Critical Analysis of Sentencing Practices under Indonesia’s Criminal Justice System - Seno Aji, Nandito (Jurnal Hukum In Concreto, 2025)
This research aims to analyze the forms of judicial inconsistency in sentencing theft cases, particularly those involving juvenile offenders, and to identify the contributing factors within Indonesia’s criminal justice framework. Sentencing disparity often raises serious concerns regarding substantive justice and legal certainty, especially when two cases with nearly identical legal elements and factual backgrounds result in significantly different judgments. This study employs a normative juridical method combined with a case study approach, focusing on two court decisions: Number 14/Pid.B/2011/PN.Yk and Number 10/Pid.SUS-Anak/2015/PN.Yk. Data were collected from statutory instruments, court documents, and judicial reasoning, and analyzed through both normative and sociological lenses. The findings reveal that judicial inconsistency stems from differences in the legal basis applied by judges, the social backgrounds of the offenders, and the uneven consideration of social inquiry reports. Moreover, the unregulated scope of judicial discretion due to the absence of standardized sentencing guidelines has significantly contributed to these disparities. When sentencing is not grounded in clear legal, sociological, and philosophical justification, the ruling loses its legitimacy and may erode public trust in the justice system. This study emphasizes the urgent need for a national sentencing guideline to ensure more consistent, transparent, and accountable sentencing practices within Indonesia’s legal system, particularly in cases involving vulnerable groups such as juveniles.